A spectrally selective visible microbolometer based on planar subwavelength thin films. Issue 7 (10th March 2023) - Xu, Qianqian; Zhou, Ziji; Tan, Chong; Pan, Xiaohang; Wen, Zhengji; Zhang, Jinguo; Zhou, Dongjie; Sun, Yan; Chen, Xin; Zhou, Lei; Dai, Ning; Chu, Junhao; et al.
Abstract : A metal–insulator–metal (MIM) planar trilayer thin-film nanostructure was used to realize a bolometric detector, which features compact design, simple structure and cost-efficiency. Abstract : In this work, we experimentally demonstrate a new type of compact, low-cost, visible microbolometer based on metal–insulator–metal (MIM) planar subwavelength thin films, which exploits resonant absorption for spectral selectivity without additional filters and has the advantages of compact design, simple structure, cost-efficiency, and large format fabrication. The experimental results show that a proof-of-principle microbolometer exhibits spectrally selective properties in the visible frequency range. At a resonant absorption wavelength of 638 nm, a responsivity of about 10 mV W −1 is achieved at room temperature at a bias current of 0.2 mA, which is about one order of magnitude higher than that of the control device (a bare Au bolometer). Our proposed approach provides a viable solution for the development of compact and inexpensive detectors.